2015
DOI: 10.1073/pnas.1517629112
|View full text |Cite
|
Sign up to set email alerts
|

Bursts of beta oscillation differentiate postperformance activity in the striatum and motor cortex of monkeys performing movement tasks

Abstract: Studies of neural oscillations in the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) have demonstrated modulations in beta-band power associated with sensory and motor events on time scales of 1 s or more, and have shown that these are exaggerated in Parkinson's disease. However, even early reports of beta activity noted extremely fleeting episodes of beta-band oscillation lasting <150 ms. Because the interpretation of possible functions for beta-band oscillations depends st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
402
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(429 citation statements)
references
References 42 publications
26
402
1
Order By: Relevance
“…To further evaluate the changes at specific frequency bands, we calculated the normalized spectrum before, during, and after laser stimulation. We found that optogenetic stimulation of SChIs robustly increased oscillation power across higher frequency bands conventionally defined as alpha (8)(9)(10)(11)(12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), low gamma (30-60 Hz), and high gamma (60-100 Hz), but not lower frequency bands of delta (1-4 Hz) or theta (4-8 Hz) (Fig. 2 E and F; n = 7 mice).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…To further evaluate the changes at specific frequency bands, we calculated the normalized spectrum before, during, and after laser stimulation. We found that optogenetic stimulation of SChIs robustly increased oscillation power across higher frequency bands conventionally defined as alpha (8)(9)(10)(11)(12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), low gamma (30-60 Hz), and high gamma (60-100 Hz), but not lower frequency bands of delta (1-4 Hz) or theta (4-8 Hz) (Fig. 2 E and F; n = 7 mice).…”
Section: Resultsmentioning
confidence: 85%
“…Beta oscillations are also found in the CBT circuits of patients with other movement-related disorders, such as epilepsy and dystonia (6,7), and in normal, nonhuman primates (8,9) and normal rodents (10,11). Moreover, brief elevations (≤200 ms) of beta oscillations are observed in the basal ganglia of task-performing nonhuman primates and rodents during specific phases of behavioral tasks (10,12,13), indicating that beta oscillations may be important for motor and nonmotor functions. In contrast to the regulated temporal variability of beta oscillations in normal motor functions, temporal stability is correlated with the parkinsonian motor symptoms of bradykinesia and rigidity (2).…”
mentioning
confidence: 99%
“…We show that nonaveraged spontaneous beta activity in SI and frontal cortex emerges as brief events that typically last <150 ms (1,30). These beta events co-occur with varying levels of alpha activity, depending on the subject and area studied.…”
Section: Discussionmentioning
confidence: 80%
“…However, burst-like or intermittent periods of high beta power occurring stochastically within the time-averaged period could appear as continuous rhythms in averaged spectrograms, despite not ever actually being sustained. Several recent studies have shown that in nonaveraged data beta oscillations often emerge transiently, typically lasting <150 ms (2,4,(30)(31)(32).…”
mentioning
confidence: 99%
“…2F). We further applied NMHS decoding to local field potential (LFP) activity recorded in the putamen, caudate nucleus and motor cortex of monkeys performing reaching tasks (27). NMHS decoding demonstrated region-specific LFP synchronization between the putamen and motor cortex, which are known to be anatomically connected (Fig.…”
Section: Significancementioning
confidence: 99%